Research on the Intervention and Prevention of College Students' Mental Health Crisis From the Perspective of Ideological and Physical Education - Yu, Jiang (Frontiers in Public Health, 2022)
Present study has aimed to understand the intervention and prevention of the mental health crisis of college students. For this purpose, this study has checked the effect of trust in well-being information on preventive behavior and mental well-being. The target population taken for this study is the students of colleges situated in Mainland in China. The data was collected from the 458 students of the college. Smart PLS has been employed on the data to get the results using partial least square structural equation modeling. For this purpose, the data were analyzed in two stages, i.e. measurement model stage and the structural model stage. Results of this study have revealed that trust in well-being information plays a significant and positive role in setting preventive behavior and the mental well-being of students. Further, it has also been revealed that preventive behavior also plays a significant and positive role in mental well-being. Additionally, preventive behavior has been found as an important mediating variable among the relationship of trust in well-being information and mental well-being. Moreover, family support is crucial by positively moderating the relationship between preventive behavior and mental well-being. Many practical implications have been found among which the foremost is that the education institutes must undertake those efforts that aim to ensure the fairness in the information spread regarding the mental well-being during seminars, workshops and administration should play a positive role responsible for strengthening the mental health of students by changing managing ideas, improving student education management, innovating management techniques and methods, and promoting the development and progress of education management for college students.